Deep Learning and Inquiry Approach for Enhancing Learning Outcomes of College Students - Mochamad Muchson; Irawan Hadi Wiranata; M Anas; Rr Forijati; Hariyono Hariyono; Herdian Tria Wulan Sari; Surya Ayu Azizah (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study examines the effect of integrating Inquiry-based learning with a pedagogical Deep Learning approach on students’ learning outcomes in a Learning Planning course. Methodology: Employing a one-group pretest–posttest quantitative design, the study involved N = 50 undergraduate students from two teacher education institutions in East Java, Indonesia, involving Economics Education students from Universitas Nusantara PGRI Kediri and Universitas PGRI Mpu Sindok Nganjuk. The instructional intervention emphasized Inquiry activities aligned with Deep Learning principles mindful, meaningful, and joyful learning. Main Findings: Data were collected using a validated learning outcomes test administered before and after the intervention and analyzed through paired-sample t-tests. The findings indicate a statistically significant improvement in students’ learning outcomes, with mean scores increasing from 73.40 (pretest) to 84.80 (posttest), yielding an average gain of 11.4 points (p < 0.05). Novelty/Originality of this study: These results suggest that the integration of Inquiry-based learning and Deep Learning principles holds potential for enhancing pedagogical competence in Learning Planning courses within teacher education programs.